2004
DOI: 10.1063/1.1641168
|View full text |Cite
|
Sign up to set email alerts
|

Composite nanogranular films of FePt-MgO with (001) orientation onto glass substrates

Abstract: Articles you may be interested inTemperature dependence and magnetocrystalline anisotropy studies of self-assembled L 1 0 -Fe 55 Pt 45 ferromagnetic nanocrystals Activation volume and magnetization reversal of nanoparticle films composed of magnetically isolated Fe-Pt nanoparticles J. Appl. Phys. 97, 10J321 (2005); 10.1063/1.1861274 Size effect on L 1 0 ordering and magnetic properties of chemically synthesized FePt and FePtAu nanoparticles J. Appl. Phys. 97, 10J310 (2005); 10.1063/1.1852314 Structural and mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Different methods such as high energy ion bombardment [3], adding a nonmagnetic element [4], and annealing [5] have been employed to alter and improve the magnetic properties for magnetic media applications. In this paper, moderate ion-beam bombardment and post annealing was used to investigate the phase evolution of Fe/Pt multilayers, and correlate it with the magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods such as high energy ion bombardment [3], adding a nonmagnetic element [4], and annealing [5] have been employed to alter and improve the magnetic properties for magnetic media applications. In this paper, moderate ion-beam bombardment and post annealing was used to investigate the phase evolution of Fe/Pt multilayers, and correlate it with the magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Since most applications for high density media require a proper particle size (Ͻ9 nm in diameter), the size effect of FePt nanoparticles on the phase transformation from the disordered A1 FePt (fcc) to the ordered L1 0 FePt (fct) structure becomes an important issue. 4 Studies have shown that there is a strong size effect on the ordering of FePt nanoparticles, and that small fcc FePt nanoparticles need much longer time to complete ordering upon isothermal annealing.…”
mentioning
confidence: 99%
“…Numerous studies on FePt granular films have been conducted so far. [5][6][7] However, most of the films reported so far were with random crystal orientation and too thick, obviously inappropriate for magnetic recording.…”
Section: Introductionmentioning
confidence: 99%